Liberalism or Republicanism by Kant? - Horn, Christoph (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Should we assign Kant’s political philosophy rather to the tradition of liberalism or to that of republicanism? Prima facie one might think that liberalism must be the right classification since Kant emphasizes, in his Doctrine of Right, the original, innate right to freedom. Many interpreters believe that he, thereby, wants to express the primacy of human rights. In this article, however, I argue that Kant’s political philosophy should be seen as a combination of elements taken from liberalism as well as from republicanism. It holds even true that the more fundamental aspects are derived from the tradition of republicanism. If we look at ancient and early modern forms of republicanism, we see that the peculiar way in which Kant formulates his normative individualism mirrors his preference for the republican tradition.